2021
DOI: 10.1002/pro.4152
|View full text |Cite
|
Sign up to set email alerts
|

CyDisCo production of functional recombinant SARS‐CoV‐2 spike receptor binding domain

Abstract: The COVID‐19 pandemic caused by SARS‐CoV‐2 has applied significant pressure on overtaxed healthcare around the world, underscoring the urgent need for rapid diagnosis and treatment. We have developed a bacterial strategy for the expression and purification of a SARS‐CoV‐2 spike protein receptor binding domain (RBD) that includes the SD1 domain. Bacterial cytoplasm is a reductive environment, which is problematic when the recombinant protein of interest requires complicated folding and/or processing. The use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…However, RBD-specific Abs titers increased after the second vaccine boost ( Yang et al, 2020 ). Some recent studies have shown that the efficient production of SARS-CoV-2 RBD in E. coli may imply the refolding (with buffer containing L-arginine, glutathione, glutathione disulfide, urea) or co-expression of sulfhydryl oxidase and disulfide isomerase to rebuild the disulfide bonds of the target protein ( He et al, 2021 ; Prahlad et al, 2021 ). The results of the current research have demonstrated the low immunogenicity of recombinant RBD and the fact that two immunizations are insufficient to provide the required RBD-specific Abs titers, even in the case of immunization with adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…However, RBD-specific Abs titers increased after the second vaccine boost ( Yang et al, 2020 ). Some recent studies have shown that the efficient production of SARS-CoV-2 RBD in E. coli may imply the refolding (with buffer containing L-arginine, glutathione, glutathione disulfide, urea) or co-expression of sulfhydryl oxidase and disulfide isomerase to rebuild the disulfide bonds of the target protein ( He et al, 2021 ; Prahlad et al, 2021 ). The results of the current research have demonstrated the low immunogenicity of recombinant RBD and the fact that two immunizations are insufficient to provide the required RBD-specific Abs titers, even in the case of immunization with adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the 2019 SARS-CoV-2 pandemic, RBD that is the key domain for human cell infection [ 19 , 20 ] has attracted much attention as a target molecule for treatment utilizing neutralizing antibodies [ 21 , 22 ] and vaccines [ 23 ]. In this context, recombinant expression of RBD in E. coli has been attempted; however, expression without the presence of any solubility-enhancing tag within the soluble fraction and with correct folding has not yet been achieved [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. RBD possesses four disulfide bonds [ 33 ] that make it difficult for this domain to fold correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Although many attempts have been made to refold RBDs from inclusion bodies, the procedure is complicated, and it has been suggested that the physicochemical properties may differ from those of proteins produced by baculovirus or by mammalian cell expression systems [ 31 ]. Although the RBD-MBP fusion protein was reported to be expressed in the soluble fraction of the cytoplasm [ 32 ], there was no structural or physicochemical information for the recombinant fusion protein except for information regarding ACE2 binding ability, and it may be possible that untagged RBD is insoluble when MBP is cleaved due to the strong solubilizing effect of MBP [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have shown that Spike RBD can be obtained in soluble form from E. coli after a denaturation/refolding procedure and/or by using genetically modified strains with reducing cytoplasm [12], [13], [14], [15], [16]. In any case, in all studies were Spike RBD has been obtained from E. coli the antigen seems to have limited antigenicity and low yield [12]. This may explain why there is no report of an accurate immunoassay, validated with a large cohort of samples, which uses Spike RBD produced in E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of glycosylation systems and the reducing environment typically found in the bacterium cytoplasm results in formation of insoluble inclusion bodies upon expression of Spike in E. coli [11]. Some researchers have shown that Spike RBD can be obtained in soluble form from E. coli after a denaturation/refolding procedure and/or by using genetically modified strains with reducing cytoplasm [12], [13], [14], [15], [16]. In any case, in all studies were Spike RBD has been obtained from E. coli the antigen seems to have limited antigenicity and low yield [12].…”
Section: Introductionmentioning
confidence: 99%